Improved recellularization of ex vivo vascular scaffolds using directed transport gradients to modulate ECM remodeling. Issue 7 (29th April 2013) - Tosun, Zehra; McFetridge, Peter S.
Abstract The regeneration of functional, clinically viable, tissues from acellular ex vivo tissues has been problematic largely due to poor nutrient transport conditions that limit cell migration and integration. Compounding these issues are subcellular pore sizes that necessarily requires extracellular matrix (ECM) remodeling in order for cells to migrate and regenerate the tissue. The aim of the present work was to create a directed growth environment that allows cells to fully populate an ex vivo‐derived vascular scaffold and maintain viability over extended periods. Three different culture conditions using single (one nutrient source) or dual perfusion bioreactor systems (two nutrients sources) were designed to assess the effect of pressure and nutrient gradients under either low (50/30 mmHg) or high (120/80) relative pressure conditions. Human myofibroblasts were seeded to the ablumenal periphery of an ex vivo‐derived vascular scaffold using a collagen/hydrogel cell delivery system. After 30 days culture, total cell density was consistent between groups; however, significant variation was noted in cell distribution and construct mechanics as a result of differing perfusion conditions. The most aggressive transport gradient was developed by the single perfusion low‐pressure circuits and resulted in a higher proportion of cells migrating across the scaffold toward the vessel lumen (nutrient source). These investigations illustrate the influence of directed nutrient gradients where precisely controlled perfusion conditions significantly affects cell migration, distribution and function, resulting in pronounced effects on construct mechanics during early remodeling events. Biotechnol. Bioeng. 2013; 110: 2035–2045. © 2013 Wiley Periodicals, Inc.